Beyond Medicine : Why European Social Democracies Enjoy Better Health Outcomes Than the United States - Dutton, Paul V. (Book collections on Project MUSE., 2021)
"In this book Paul Dutton argues that Europeans are healthier than Americans because of Europe's historical commitment to improve the social determinants of health. Dutton divides his book into three stages of life: birth and childhood; adulthood and working years; and post-labor market participation or retirement. For each of these phases Dutton compares the U.S. with a different European nation: France for babies and children, Germany for working-age adults, and Sweden for senior citizens."--